SOCIO-EMOTIONAL DEVELOPMENT THE ESSENCE OF DIGITAL-BASED CIVICS LEARNING TOBELO HALUT PRESIDENTIAL ELEMENTARY SCHOOL - Aulia Warye; Siti Inganah; Daroe Iswatiningsih (RADJA PUBLIKA, 2025)
This study used a descriptive questionnaire to examine the social-emotional development of fifth grade students in digital-based Citizenship Education (PKn) learning at SD Inpres I Tobelo, North Halmahera. Digital-based PKn learning is a necessity in the era of digital transformation, but its impact on students' social-emotional development has not been widely studied, especially in the context of basic education in the 3T (Frontier, Outermost, and Disadvantaged) areas. Based on the results of the study, students' social-emotional development is positively influenced by the implementation of digital-based PKn learning, especially in terms of collaboration skills, digital empathy, and learning independence. However, there are obstacles in the form of a digital divide, changes in direct interaction patterns, and limited infrastructure. By utilizing digital technology to integrate social-emotional elements in PKn learning, this study produces an integrative learning model with five main components: (1) digital readiness assessment, (2) technology-assisted collaborative learning, and (3) technology-assisted collaborative learning. learning, (3) digital social reflection, (4) digital citizenship simulation, and (5) social project-based evaluation. The implications of this research provide a theoretical and practical basis for the development of digital citizenship.